Innovation on Preventing the Covid-19 Spread Using "Cool" Personal Protective Clothing for Healthcare Workers - Ciptadhi Tri Oka Binartha; Muhammad Burhannudinnur; Awang Eka Novia Rizali; Mustamina Maulani; Hamid Nurrohman (Media Kesehatan Masyarakat Indonesia, 2021)
Healthcare workers need Personal Protective Equipment (PPE) that can protect them, to be safer and more comfortable with handling COVID-19 patients. One important PPE is the Personal Protective Clothing (PPC), where the PPC design has to comply with regulatory requirements, in terms of application, safety, comfort, and cost. A disadvantage is that PPC can be hot and poorly ventilated. The objective of innovation research was to developed a new design of PPC with safe, cool, and comfortable personal protective clothing. PPC is made with 100% polyester coverall according to WHO standards and with ice pack design. This product was subsequently analyzed for material morphology and penetration (water-repellent). Further, relevant information was captured from 14 participants in several health professions, using questionnaires. The laboratory test results of the sample materials reportedly surpassed the specifications and were also incorporated into level-3 PPC. Based on the survey data, the personal protective clothing with ice pack was simple, comfortable, and not hot to use for healthcare workers.